PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TEAM ASSISTED INDIVIDUALIZATION DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG BANGUN DATAR SISWA KELAS V SD NEGERI 1 KALENG TAHUN 2014 - Setiyowati, Sekar Aris (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The purpose of this study is: (1) to describe the using of Team Assisted Individualization Cooperative Learning models in improvement the Math learning about Geometric shapes; (2) to describe that the using of Team Assisted Individualization Cooperative Learning models can improving the math learning result about geometric shapes. This research is classroom action research (CAR) . The result show that 1) the using of Team Assisted Individualization Cooperative Learning models can be successful , 2) the using of Team Assisted Individualization Cooperative Learning models can improving the match learning from pre test to cycle 1 until cycle 3. Key words: Team Assisted Individualization, mathematic studies,the five grade